2015
DOI: 10.1007/s10897-015-9906-9
|View full text |Cite
|
Sign up to set email alerts
|

Review of Commercially Available Epilepsy Genetic Panels

Abstract: Next generation sequencing panels have revolutionized the diagnostic approach to patients with epilepsy. There are several commercial epilepsy panels available. We assessed the list of genes tested and consent forms for epilepsy panels available at seven laboratories. The panels varied in the number of genes included (70-465 genes). In some panels, genes not currently associated with epilepsy were included (up to 4 % of panel content). The panels also included genes for lysosomal storage disorders (6-12 %), co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 10 publications
(11 reference statements)
2
48
0
1
Order By: Relevance
“…Both assessed HTS panels were cost‐effective compared to the standard diagnostic model with a cost saving of AU$7,535 (95% CI: $2,278; $22,188) and AU$16,387 (95% CI: $9,782; $35,120) per additional diagnosis (Table and Figure ). The anticipated diagnostic yields reflect recent similar reported results (Mercimek‐Mahmutoglu et al., ; Trump et al., ), and demonstrated that a larger number of genes in a panel did not equate to a higher diagnostic yield, reflecting the importance of a tightly curated gene list (Chambers et al., ). For example, not all panels included the recently described EE genes DNM1 (616346), DYNC1H1 (614563), and WWOX (616211).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Both assessed HTS panels were cost‐effective compared to the standard diagnostic model with a cost saving of AU$7,535 (95% CI: $2,278; $22,188) and AU$16,387 (95% CI: $9,782; $35,120) per additional diagnosis (Table and Figure ). The anticipated diagnostic yields reflect recent similar reported results (Mercimek‐Mahmutoglu et al., ; Trump et al., ), and demonstrated that a larger number of genes in a panel did not equate to a higher diagnostic yield, reflecting the importance of a tightly curated gene list (Chambers et al., ). For example, not all panels included the recently described EE genes DNM1 (616346), DYNC1H1 (614563), and WWOX (616211).…”
Section: Discussionsupporting
confidence: 81%
“…Although the cost of ES is falling, limited diagnostic budgets and concerns regarding the chance of detecting an incidental finding (IF) may mean that families and clinicians prefer to order a HTS gene panel (Chambers et al., ) over ES. Simpler genetic counseling (with a time and cost saving) is required for a panel than ES (Chambers et al., ). We therefore compared the cost and anticipated diagnostic yield of two commercial HTS EE panels with the SDM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, targeted capture using NGS panels have been used in both research and clinical molecular genetics laboratories to understand the molecular etiology of epilepsy disorders53. The NGS panels used in research studies vary in gene composition, sample size, inclusion criteria, and sequence analytic protocol.…”
Section: Discussionmentioning
confidence: 99%